Question #d20c5 Algebra Expressions, Equations, and Functions Variable Expressions 1 Answer RHallock · Stefan V. May 5, 2017 (2(3)+5(2))/(2-3)2(3)+5(2)2−3 =(6+10)/(-1)=6+10−1 =16/(-1)=16−1 =-16=−16 Explanation: You substitute the corresponding value for each variable. Once you've done that--solve. :-) Answer link Related questions How do you write the variable expression for: a quotient of 2 and the sum of a number and 3 ? What are variables? What are variable expressions? How do you write variable expressions? How do you evaluate variable expressions? How do you simplify the expression 3x-x+43x−x+4? How do you write a quotient of a number and 6 as an expression? How do you evaluate the expression 2x+12x+1 for x=1x=1? How do you write a product of a number and 2 as an expression? How do you write 5 less than 2 times a number as a variable expression? See all questions in Variable Expressions Impact of this question 1319 views around the world You can reuse this answer Creative Commons License